Negative and positive interactions among plants: effect of competitors and litter on seedling emergence and growth of forest and grassland species - Loydi, Alejandro (2015)
Living plant neighbours, but also their dead aboveground remains (i.e. litter), may individually exert negative or positive effects on plant recruitment. Although living plants and litter co-occur in most ecosystems, few studies have addressed their combined effects, and conclusions are ambivalent. Therefore, we examined the response in terms of seedling emergence and growth of herbaceous grassland and forest species to different litter types and amounts and the presence of competitors. We conducted a pot experiment testing the effects of litter type (grass, oak), litter amount (low, medium, high) and interspecific competition (presence or absence of four Festuca arundinacea individuals) on seedling emergence and biomass of four congeneric pairs of hemicryptophytes from two habitat types (woodland, grassland). Interactions between litter and competition were weak. Litter presence increased competitor biomass. It also had positive effects on seedling emergence at low litter amounts and negative effects at high litter amounts, while competition had no effect on seedling emergence. Seedling biomass was negatively affected by the presence of competitors, and this effect was stronger in combination with high amounts of litter. Litter affected seedling emergence while competition determined the biomass of the emerged individuals, both affecting early stages of seedling recruitment. High litter accumulation also reduced seedling biomass, but this effect seemed to be additive to competitor effects. This suggests that live and dead plant mass can affect species recruitment in natural systems, but the mechanisms by which they operate and their timing differ.